2007
DOI: 10.1128/iai.00095-07
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Dendritic Cell Maturation by Malaria Is Dose Dependent and Does Not RequirePlasmodium falciparumErythrocyte Membrane Protein 1

Abstract: Red blood cells infected with Plasmodium falciparum (iRBCs) have been shown to modulate maturation of human monocyte-derived dendritic cells (DCs), interfering with their ability to activate T cells. Interaction between Plasmodium falciparum erythrocyte membrane protein 1 (PfEMP1) and CD36 expressed by DCs is the proposed mechanism, but we show here that DC modulation does not require CD36 binding, PfEMP1, or contact between DCs and infected RBCs and depends on the iRBC dose. iRBCs expressing a PfEMP1 variant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
114
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(131 citation statements)
references
References 58 publications
14
114
0
3
Order By: Relevance
“…These findings were taken further to show that this process involved the binding of iRBC to CD36 on DCs [24], which is a multiligand scavenger receptor known to bind apoptotic cells, against which immune responses are often not desired. More recent in vitro studies have shown additional suppressive effects not involving parasite binding to CD36 but implicating chondroitin sulphate-A, and also noncontact mechanisms [25]. Furthermore, this study showed that high doses of parasites (100 iRBC:1 DC) were suppressive and caused DC apoptosis, whilst low doses (10:1) activated DCs.…”
Section: Dendritic Cells and Malariasupporting
confidence: 50%
See 1 more Smart Citation
“…These findings were taken further to show that this process involved the binding of iRBC to CD36 on DCs [24], which is a multiligand scavenger receptor known to bind apoptotic cells, against which immune responses are often not desired. More recent in vitro studies have shown additional suppressive effects not involving parasite binding to CD36 but implicating chondroitin sulphate-A, and also noncontact mechanisms [25]. Furthermore, this study showed that high doses of parasites (100 iRBC:1 DC) were suppressive and caused DC apoptosis, whilst low doses (10:1) activated DCs.…”
Section: Dendritic Cells and Malariasupporting
confidence: 50%
“…The capacity of murine splenic CD11c + DCs to become activated and to present antigen to T cells is believed to change over the course of infection [25,40,42], and this observation may reconcile some of the heterogenous findings that showed either activation or suppression of DC function associated with malaria. In simple terms, early on in infection when parasite density is relatively low, IL-12-mediated mechanisms induce IFN-γ-producing CD4 + T cells.…”
Section: Dendritic Cells and Malariamentioning
confidence: 91%
“…Conversely, lipopolysaccharide (LPS)‐stimulated dendritic cells (DCs) responded appropriately 110. This immunomodulation of DCs by iRBCs was initially thought to depend on P. falciparum erythrocyte membrane protein (PfEMP)‐1; 110,111 however, ‘stunning’ of DCs was later shown to be PfEMP‐1‐independent 112. Subsequent reports showed a role of hemozoin in the functional impairment of DCs and monocyte/macrophages 108.…”
Section: Mechanisms Of Reduced Inflammation At High Exposure Levelsmentioning
confidence: 99%
“…fungi and some protozoans) do not and have to face the immune system during their lifetime in the host organism. Perturbing DC differentiation and/or maturation is a strategy that is obviously followed by some slowly dividing pathogens as shown by the examples of Mycobacterium leprae (34) and Plasmodium falciparum (35). Although the mechanism used by M. leprae is still not clear, recent work has shown that red blood cells infected by P. falciparum are able to prevent both DC activation and the triggering of a Th1 response (35).…”
Section: Chitosan Does Not Prevent Restimulation Of Dcs Butmentioning
confidence: 99%
“…Perturbing DC differentiation and/or maturation is a strategy that is obviously followed by some slowly dividing pathogens as shown by the examples of Mycobacterium leprae (34) and Plasmodium falciparum (35). Although the mechanism used by M. leprae is still not clear, recent work has shown that red blood cells infected by P. falciparum are able to prevent both DC activation and the triggering of a Th1 response (35). It has been shown that this effect can be mediated by the binding of an endogenous glycan, chondroitin sulfate A, to the surface of infected red blood cells (35).…”
Section: Chitosan Does Not Prevent Restimulation Of Dcs Butmentioning
confidence: 99%